Wergild, Compensation and Penance
1 online resource.
Keywords: This volume offers the first comprehensive account of the monetary logic that guided the payment of wergild and blood money in early medieval conflict resolution. In the early middle ages, wergild played multiple roles: it was used to measure a person's status, to prevent and end conflicts, and to negotiate between an individual and the agents of statehood. This collection of interlocking essays by historians, philologists and jurists represents a major contribution to the study of law and society in Western Europe during the early Middle Ages. Contributors are Lukas Bothe, Warren Brown, Stefan Esders, Wolfgang Haubrichs, Paul Hyams, Tom Lambert, Ralph W. Mathisen, Rob Meens, Han Nijdam, Lisi Oliver, Harald Siems, Karl Ubl, and Helle Vogt.